E-xperience in E-learning: The Impact of a Peer Assisted Online Mentoring Scheme on an E-learning Programme: A Case Study of E-College Wales - Davies, Ian (Proceedings of the International Conference on Networked Learning, 2004)
An independent evaluation of E-College Wales was carried out in spring 2003, to assess and consider the vision of e-learning within the University of Glamorgan from the viewpoint of students and staff. One of the main findings from this evaluation was the need for an enhanced support framework that satisfied the needs of the student. Many students articulated the need for a mentoring system, designed to support first year students. This research paper will therefore evaluate the implementation of a peer assisted online mentoring scheme (PAL – Online), highlighting a gap in the current literature concerning student support in relation to e-learning and establishes a need for further investigation into how mentoring schemes such as PAL – Online can enhance the e-learning experience for both student and teacher.